Physical therapy: tutorial guide - Епифанов, В. А. лечебная физкультура, физиотерапия Виталий Александрович (Tutorial guide, 2020)
This tutorial guide was prepared by lead experts in the field of physical therapy in accordance with the new program for students (trainees) of medical universities (Medical Rehabilitation, section Therapeutic Physical Culture). It takes into account modern achievements of medical science, which have led to a change in views on the methodology of rehabilitation treatment. Clinical and physiological substantiation of the use of therapeutic physical culture in complex therapy of patients and persons with disabilities is presented in sufficient details. The book is based on the modern principles of prescribing various means of physical therapy using motor mode, massage, manual and psychotherapy, occupational therapy, hippotherapy, kinesiotherapy, etc. The methods that are most widely used in various diseases and injuries of the central and peripheral nervous, cardiovascular and musculoskeletal systems, respiratory organs, metabolism, and other metabolic diseases are widely covered and presented in the rehabilitation programs. Each chapter includes clinical symptoms and diagnosis of the underlying disease (damage), which enables to customize the rehabilitation programs. The tutorial guide is perfectly illustrated, contains a large number of diagrams and tables, some sections provide complexes or a list of special physical exercises. The edition is intended for students of medical universities studying in the specialties of General Medicine and Pediatrics in the discipline of Medical Rehabilitation, trainees of postgraduate education departments, interns, clinical residents, graduate students, and will also be useful for specialists working in practical healthcare.